Assessing Studentsâ Spiritual Practice in IIUM (International Islamic University of Malaysia) - Radzi, Farhana Mohamad; Sawari, Siti Salwa Md; Ghazali, Mohd Al Ã¢Â€Â™Ikhsan (ASPENSI, 2016)
ABSTRACT: Spirituality was highly valued in the teaching and learning process in Malaysia. The MoE (Ministry of Education) Malaysia has incorporated elements of Islamic and Moral Education in the education system in Malaysia. This is done to generate a balanced individual and overall potential development of the physical, emotional, spiritual and intellectual beliefs, and devotion to Allah. Thus, the objective of this study is to determine the spiritual practice experienced by IIUM (International Islamic University of Malaysia) students. This study used qualitative method, and process of data collection is done through interview techniques. The interview techniques are able to provide a framework within which respondents can express their understanding and knowledge of their own manner. These findings clearly indicate that the daily or weekly spiritual practice performed by IIUM students is such as five daily practices for spiritual development: prayer, meditation, service, recite the Al-Qurâan, and integrity. Prayer, recite the Al-Qurâan, and meditation feed the spirit; while integrity and service exercise will develop the strength and capacities as Muslim. Together they constitute the injunctions one is to follow to develop spiritually. KEY WORD: Spiritual practice, Muslim student, assessment, Islamic and moral education, prayer, meditation, service, recite the Al-Qurâan, and integrity. ABSTRAKSI: âPenilaian Amalan Rohani Pelajar di UIAM (Universiti Islam Antarabangsa Malaysia)â. Kerohanian adalah nilai yang tinggi dalam proses pengajaran dan pembelajaran di Malaysia. KPM (Kementerian Pelajaran Malaysia) telah menggabungkan unsur-unsur Pendidikan Moral dan Islam dalam sistem pendidikan di Malaysia. Ini dilakukan untuk menjana pembangunan yang seimbang bagi individu dan keseluruhan potensi jasmani, emosi, rohani dan intelek, dan kepatuhan kepada Allah. Oleh itu, objektif kajian ini adalah untuk menentukan pengalaman amalan rohani oleh pelajar-pelajar UIAM. Kajian ini menggunakan kaedah kualitatif, dan proses pengumpulan data dilakukan melalui teknik temuduga. Teknik temuduga dapat menyediakan rangka kerja yang membolehkan responden dapat meluahkan pemahaman dan pengetahuan tentang mereka dan cara mereka sendiri. Penemuan ini jelas menunjukan bahawa amalan harian atau mingguan rohani yang dilakukan oleh pelajar UIAM adalah lima amalan setiap hari untuk pembangunan rohani, seperti: doa, meditasi, perkhidmatan, membaca Al-Quran, dan integriti. Sholat, membaca Al-Quran, dan meditasi memberi makanan rohani; manakala integriti dan menjalankan perkhidmatan akan membangunkan kekuatan dan kapasiti sebagai orang Islam. Bersama-sama ianya membentuk injunksi seseorang untuk mengikuti dan membangunkan rohani.KATA KUNCI: Amalan rohani, pelajar Islam, penilaian, pendidikan moral dan Islam, doa, meditasi, perkhidmatan, membaca Al-Quran, dan integriti.Â Â Â Â About the Authors: Farhana Mohamad Radzi is a Lecturer at the Kulliyah of Education IIUM (International Islamic University of Malaysia) in Gombak, Kuala Lumpur, Malaysia. Siti Salwa Md Sawari is a Doctor of Philosophy Candidate (Generic) at the Faculty of Islamic Civilization UTM (Malaysia University of Technology) in Kuala Lumpur 54100, Malaysia. Mohd Al-âIkhsan Ghazali is a Lecturer at the Faculty of Islamic Civilization UTM (Malaysia University of Technology) in Kuala Lumpur 54100, Malaysia. Their e-mail addresses are: farhana.radzi@gmail.com, salwa.sawari@gmail.com and alikhsan@ic.utm.myHow to cite this article? Radzi, Farhana Mohamad, Siti Salwa Md Sawari & Mohd Al-âIkhsan Ghazali. (2016). âAssessing Studentsâ Spiritual Practice in IIUM (International Islamic University of Malaysia)â in INSANCITA: Journal of Islamic Studies in Indonesia and Southeast Asia, Vol.1(1), February, pp.121-126. Bandung, Indonesia: Minda Masagi Press, ISSN 2443-1776. Chronicle of the article: Accepted (December 1, 2015); Revised (January 10, 2016); and Published (February 5, 2016).